Monolithic Zirconia Partial Coverage Restorations: An In Vitro Mastication Simulation Study. Issue 1 (2nd December 2020) - Gupta, Savita; Abdulmajeed, Awab; Donovan, Terry; Boushell, Lee; Bencharit, Sompop; Sulaiman, Taiseer A.
Abstract: Purpose: To evaluate the survival rate (fatigue resistance), bonding efficiency and marginal integrity of monolithic zirconia partial and full coverage single restorations adhesively bonded to the tooth structure using air‐particle abrasion, a primer with 10‐methacryloyloxydecyl dihydrogen phosphate and a composite‐resin cement (APC) protocol. Materials and Methods: Extracted human premolars (N = 32) were randomly divided into four groups of eight specimens each. Premolars were prepared for the following restorations: full crown (group 1, control), mesial‐occlusal‐distal‐facial onlay (MODF, group 2) preserving 2 mm facio‐lingual functional cusp width, mesial‐occlusal‐distal‐lingual onlay (MODL, group 3) preserving 2 mm facio‐lingual nonfunctional cusp width, mesial‐occlusal‐distal‐buccal‐lingual onlay (MODBL, group 4), overlay preparation. All restorations were milled from monolithic 3 mol% yttria (3Y) zirconia blocks (ZirCad, A1 LT, Ivoclar Vivadent) with CAD/CAM software presets at minimum occlusal and axial thicknesses of 1 mm. The intaglio surface of the restorations was air‐particle abraded (50 µm Al2 O3, 2‐Bar pressure, 15 s, 10 mm distance) and primed. An adhesive cement system was used to bond the restorations. Each group was subjected to thermomechanical loading for 1.2 million cycles (force = 70 N, 1.4 Hz) with simultaneous thermocycling (5‐55°C, 30 s dwell time) using a mastication simulator. All specimens were examined under scanning electron microscope (SEM) analysis (30, 100, and 150×) to evaluate cracks and marginal defects. Fracture of restoration and/or fracture within tooth structure, and debonding were considered modes of failure. Results: One specimen from group 2 debonded at 632, 000 cycles. None of the specimens failed due to fracture. SEM analysis at 30× indicated marginal integrity issue of the remaining seven intact specimens of group 2 in the area of antagonist contact. No specimens from group 1, 3, and 4 demonstrated marginal integrity issue at 30×. None of the specimens demonstrated any microcrack at 100× and150×. Conclusions: Due to its fatigue resistance, 3Y‐zirconia is a viable option for partial and full coverage single restorations. Following a strict bonding protocol, zirconia demonstrated durable adhesion to the tooth structure. Occlusal contact on restoration margins should be avoided.